Environmental impact evaluation of innovation in traditional food production lines - Osojnik Črnivec, Ilja Gasan (Acta agriculturae Slovenica, 2010)
In order to improve the knowledge on environmental impacts of current production systems and to find the solutions to reduce the negative impacts effective multi-approach environmental assessment methodologies are required. The environmental impacts assessed in complex systems, such as agriculture and food production, are prone to higher uncertainties. Therefore, field-specific standardization of the assessment procedures based on multiple screening studies are required to make the assessment outcome less vulnerable. The procedure array pairing for the formation of production step emission inventory is an important methodological process in environmental impact assessment. Initial production data was coupled with specialized databases, models found in scientific literature and environmental category characterization guidelines in order to construct an environmental impact methodological framework specific to four case studies of traditional food production.
Keywords: živilska industrija; tradicionalna živila; vplivi na okolje; environmental protection; varstvo okolja